2014
DOI: 10.7455/ijfs/3.1.2014.a1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Buckwheat Processing Products on Dough and Bread Quality Made from Whole-Wheat Flour

Abstract: The paper gives a brief overview of the current nutritional status of the Ukrainian population and describes useful buckwheat properties. The objective of the paper is to study the effect of buckwheat processing products (flour and flakes) on the technological process and quality of bread made from whole-wheat flour. This paper describes and analyzes research data on the rheological properties of dough samples which were determined by farinograph and amylograph. Investigation of structural and mechanical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…They play the most important role in absorbing and retaining water in dough. The amount of pentosans in buckwheat is higher than in wheat (Berghofer & Schoenlechner 2009;Drobot et al 2014;Wang & Zhang 2015). The higher retention capacity in sucrose solution (sucrose SRC) for buckwheat flour indicated a higher content of water-soluble pentosans in this flour.…”
Section: Resultsmentioning
confidence: 91%
“…They play the most important role in absorbing and retaining water in dough. The amount of pentosans in buckwheat is higher than in wheat (Berghofer & Schoenlechner 2009;Drobot et al 2014;Wang & Zhang 2015). The higher retention capacity in sucrose solution (sucrose SRC) for buckwheat flour indicated a higher content of water-soluble pentosans in this flour.…”
Section: Resultsmentioning
confidence: 91%
“…Glutelin was rich in histidine, threonine, valine, isoleucine, and leucine [Guao and Yao 2006]. According to Drobot et al [2014], about 80 percent of buckwheat protein comprises albumin and globulin. Cereals, in contrast, contain relatively higher levels of prolamins.…”
Section: Physicochemical Composition Of Buckwheat 9131 Proteinsmentioning
confidence: 99%
“…The buckwheat flour content had a significant negative effect on specific volume values for the xanthan gum added samples (Table 1b). In literature, there are various studies which reported the negative correlation between buckwheat flour concentration and specific volume of final product (Atalay et al 2013;Drobot et al 2014). The reason may be expounded by dilution of protein content of flour blend which is responsible for the matrix of the product structure.…”
Section: Quality Characteristicsmentioning
confidence: 99%